If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9q + 54 = 3q + 90 Reorder the terms: 54 + 9q = 3q + 90 Reorder the terms: 54 + 9q = 90 + 3q Solving 54 + 9q = 90 + 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. 54 + 9q + -3q = 90 + 3q + -3q Combine like terms: 9q + -3q = 6q 54 + 6q = 90 + 3q + -3q Combine like terms: 3q + -3q = 0 54 + 6q = 90 + 0 54 + 6q = 90 Add '-54' to each side of the equation. 54 + -54 + 6q = 90 + -54 Combine like terms: 54 + -54 = 0 0 + 6q = 90 + -54 6q = 90 + -54 Combine like terms: 90 + -54 = 36 6q = 36 Divide each side by '6'. q = 6 Simplifying q = 6
| 8+2b=10 | | 4j-4=2j+20 | | 3[5-4(4-c)]-5=5[3(5c-4)+2]-26 | | -6+y^2=10 | | x^2+.4x=.96 | | -2x^2+8x-56=0 | | 6x-9=x-4 | | -8+2a=-4 | | Y-25=-3(x-(-7)) | | 2x/3x-5/6 | | 2x^2-8x-56=0 | | 7x-2=-58 | | 5=7n-2 | | 3(x-10)-4=-6x-2 | | x-17=-12 | | -1=11+n | | 9x-13=-10+12x | | 9x-13=-10+12z | | x^16-2x^15-x^14+4x^13-x^11+x^10=0 | | 1-n=-2 | | -72=-18a | | (-x+4)(2x-1)= | | 12x^2-52x+35=0 | | 19k=-95 | | (45x^4y^10)/(9x^6y^6) | | 13=9x-5 | | 55-3T=103-7T | | 8x^2+60x-25=0 | | -14-x=-9 | | -117=-13m | | 195=13n | | -4(7-2q)+9q= |